Sterol affinity for phospholipid bilayers is influenced by hydrophobic matching between lipids and transmembrane peptides - Ijäs, H. Kristian; Lönnfors, Max; Nyholm, Thomas K.M. (Biochimica et biophysica acta, 2013)
Lipid self-organization is believed to be essential for shaping the lateral structure of membranes, but it is becoming increasingly clear that also membrane proteins can be involved in the maintenance of membrane architecture. Cholesterol is thought to be important for the lateral organization of eukaryotic cell membranes and has also been implicated to take part in the sorting of cellular transmembrane proteins. Hence, a good starting point for studying the influence of lipid–protein interactions on membrane trafficking is to find out how transmembrane proteins influence the lateral sorting of cholesterol in phospholipid bilayers. By measuring equilibrium partitioning of the fluorescent cholesterol analog cholestatrienol between large unilamellar vesicles and methyl-β-cyclodextrin the effect of hydrophobic matching on the affinity of sterols for phospholipid bilayers was determined. Sterol partitioning was measured in 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC), 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) bilayers with and without WALP19, WALP23 or WALP27 peptides. The results showed that the affinity of the sterol for the bilayers was affected by hydrophobic matching. An increasing positive hydrophobic mismatch led to stronger sterol binding to the bilayers (except in extreme situations), and a large negative hydrophobic mismatch decreased the affinity of the sterol for the bilayer. In addition, peptide insertion into the phospholipid bilayers was observed to depend on hydrophobic matching. In conclusion, the results showed that hydrophobic matching can affect lipid–protein interactions in a way that may facilitate the formation of lateral domains in cell membranes. This could be of importance in membrane trafficking. [Display omitted] ► The sterol affinity for phospholipid bilayers is affected by transmembrane peptides. ► Hydrophobic matching influences how the sterol affinity is affected by peptides. ► Peptides can both decrease and increase the sterol's affinity for the bilayer. ► Hydrophobic matching could control lateral organization in cellular membranes.